2001
DOI: 10.1097/00005053-200109000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dissociative Symptomatology and Declarative and Procedural Memory in Adolescent Psychiatric Patients

Abstract: The purpose of this study was to examine the relationship between dissociative symptomatology and declarative and procedural memory. Subjects were 41 consecutively admitted adolescent psychiatric patients, 13 to 19 years old. Each subject completed the Adolescent Dissociative Experiences Scale (A-DES). Declarative memory was assessed by the California Verbal Learning Test and procedural memory by the Tower of Toronto puzzle. All subjects were controlled for IQ and severity of psychiatric illness. Data analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…posits that dissociation is a "dis-association" of fundamental cognitive processes. A study designed to investigate the relationship between dissociative symptoms and memory found that both declarative and procedural forms of memory were associated Prohl, Resch, Parzer, & Brunner, 2001!. The authors concluded that dissociative symptoms are associated with general mnestic deficits, which correspond to the neuropsychological findings presented in Table 1. A few studies addressing neurocognitive functioning in those with dissociative dis-orders~presumably representing pathological dissociation!…”
Section: Dissociationmentioning
confidence: 70%
“…posits that dissociation is a "dis-association" of fundamental cognitive processes. A study designed to investigate the relationship between dissociative symptoms and memory found that both declarative and procedural forms of memory were associated Prohl, Resch, Parzer, & Brunner, 2001!. The authors concluded that dissociative symptoms are associated with general mnestic deficits, which correspond to the neuropsychological findings presented in Table 1. A few studies addressing neurocognitive functioning in those with dissociative dis-orders~presumably representing pathological dissociation!…”
Section: Dissociationmentioning
confidence: 70%
“…The results from many studies point out that the CDC is a useful screening instrument for assessing dissociative profiles in children. Indeed, a wide variety of studies that have utilized child and adolescent samples highlight the fact that traumatized youths present higher levels of dissociation than nontraumatized samples (Brunner et al, 2000;Calamari & Pini, 2003;Carrion & Steiner, 2000;Farrington et al, 2002;Kisiel & Lyons, 2001;Macfie et al, 2001;Prohl et al, 2001). The findings from the present study point to the importance of the assessment of dissociative symptoms in children with a history of sexual abuse.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, many studies have found a strong correlation between dissociative symptoms and a variety of traumatic experiences (Brunner, Parzer, Schuld, & Resch, 2000;Calamari & Pini, 2003;Carrion & Steiner, 2000;Farrington et al, 2002;Kisiel & Lyons, 2001;Macfie et al, 2001;Prohl, Resch, Parzer, & Brunner, 2001).…”
Section: Abstract Sexual Abuse Puerto Rican Children Dissociation mentioning
confidence: 99%
“…The level of dissociative symptoms reported by participants according to the A-DES was high compared to other adolescent clinical samples (e.g., Keck Seeley, Perosa, & Perosa, 2004;Prohl, Resch, Parzer, & Brunner, 2001;Soukap, Papežová, Kubȇna, & Mikolajová, 2010). Moreover, half of the participants (n = 9) scored high enough on the A-DES to be considered within the pathological range for dissociation (A-DES score ≥4; Kisiel & Lyons, 2001).…”
Section: Discussionmentioning
confidence: 77%